2018
DOI: 10.1007/s10654-018-0408-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of total polyphenol and polyphenol classes and the risk of colorectal cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort

Abstract: The entire manuscript is 4,120 words (including abstract (242 words), text cases, of which 3,897 were in the colon and 2,094 were in the rectum. 10Polyphenol intake was estimated using validated centre/country specific dietary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 46 publications
6
46
1
1
Order By: Relevance
“…Various mechanisms have been implicated in this protective effect of morin (ie, variation in fecal and mucosal enzymes, in tissue and serum lipids, or in Myc expression), but none of these studies investigated the expression of LMW‐PTP and apoptosis . Here we show that morin is able to lower LMW‐PTP expression in the colon mucosa in agreement with our in vitro findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Various mechanisms have been implicated in this protective effect of morin (ie, variation in fecal and mucosal enzymes, in tissue and serum lipids, or in Myc expression), but none of these studies investigated the expression of LMW‐PTP and apoptosis . Here we show that morin is able to lower LMW‐PTP expression in the colon mucosa in agreement with our in vitro findings.…”
Section: Discussionsupporting
confidence: 88%
“…Since morin is present in some fruits, one could wonder how our study relates to a modulation of cancer risk just with the diet. Dietary consumption of vegetable and fruits (both rich in polyphenolic compounds) has been associated with a lower risk of CRC, but it is thought that this beneficial effect is due to the presence in these foods of several compounds (eg, fibers, for one thing) and certainly not just to a single polyphenol like morin, which is present in small quantity in foods . In the present study morin was used since it is a potent inhibitor of LMW‐PTP in vitro, and, as we show, it also acts in vivo to lower LMW‐PTP and to decrease carcinogenesis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[64][65][66] Regarding phenolic acids, recent cohort studies ( Table 2) have focused mainly on cardiovascular disease (CVD), [67][68][69] hypertension, [70][71][72] depression, 73 metabolic syndrome, [74][75][76] diabetes, 77 and colorectal cancer. 78 A higher intake of polyphenols was associated with a statistically significant decrease in CVD risk in two studies from France and Spain, 67,69 whereas no association was found in the third. 68 In all three studies, however, flavonoid intake showed an inverse association with CVD risk, whereas no significant association was found for HCAs.…”
Section: Hydroxycinnamic Acids and Disease Risk In Epidemiological Stmentioning
confidence: 96%
“…Finally, a recently published study conducted in ten European countries has assessed the possible association between dietary polyphenol intake and the risk of colorectal cancer . Interestingly, the high intake of phenolic acids (and implicitly HCAs) was inversely associated with colon cancer in men, and positively associated with rectal cancer in women (although, when the authors applied a Bonferroni correction, none of these associations remained statistically significant; P < 002) …”
Section: Dietary Intake Of Hydroxycinnamic Acids and Associated Healtmentioning
confidence: 99%